Pengaruh Kuat Tekan Beton Dengan Menggunakan Kapur Dan Silica Fume Sebagai Bahan Tambah Semen - M. Aldi Hadrian (Jurnal Serambi Engineering, 2025)
Cement is the main material in concrete production; however, its manufacturing process generates significant CO₂ emissions that negatively affect the environment. Therefore, alternative materials are needed to partially replace cement with more environmentally friendly options. This study aims to analyze the effect of lime and silica fume on the compressive strength of concrete and compare the results with normal concrete. The research was conducted using an experimental method with three variations of concrete mixtures: normal concrete, concrete with 5% substitution of lime and silica fume, and concrete with 10% substitution based on cement weight. The results showed that normal concrete achieved an average compressive strength of approximately 20.6 MPa. At 5% substitution, the compressive strength increased to 21.258 MPa (an improvement of about 3.17%), while at 10% substitution it reached 21.898 MPa (an improvement of about 6.29%). These findings indicate that the addition of lime and silica fume can enhance the compressive strength of concrete, although the improvement is relatively minor. Further analysis is required to determine whether this difference is technically significant or merely a result of experimental variation. Overall, lime and silica fume have the potential to serve as partial cement substitutes that support the development of environmentally friendly concrete while maintaining its technical performance.